2007
DOI: 10.1063/1.2804330
|View full text |Cite
|
Sign up to set email alerts
|

Large attractive depletion interactions in soft repulsive–sphere binary mixtures

Abstract: We consider binary mixtures of soft repulsive spherical particles and calculate the depletion interaction between two big spheres mediated by the fluid of small spheres, using different theoretical and simulation methods. The validity of the theoretical approach, a virial expansion in terms of the density of the small spheres, is checked against simulation results. Attention is given to the approach toward the hard-sphere limit, and to the effect of density and temperature on the strength of the depletion pote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…Sanyal et al [24] and van Duijneveldt et al [25] were among the first to observe the fluid-solid phase transition in binary nearly-hard-sphere colloids with the size ratio 2R/ > 5, attributing it to the depletion of smaller spheres between larger spheres, an observation later extended to using polymer-coated spheres or pNIPAM nanogels as soft depletants [26,27]. A more recent theoretical study considering binary mixtures of soft repulsive spheres however predicted stronger depletion, as compared to hard spheres, and also a metastable fluid-fluid phase transition, which is yet to be verified experimentally [28]. Kaplan et al [29] and Dinsmore et al [30] reported that the fluid-solid transition for the larger spheres was promoted at a hard flat wall, due to the enhanced excluded volume effects at the wall, pointing to the importance of geometry consideration.…”
Section: Phase Separations In Binary Collodial Mixtures: Implicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Sanyal et al [24] and van Duijneveldt et al [25] were among the first to observe the fluid-solid phase transition in binary nearly-hard-sphere colloids with the size ratio 2R/ > 5, attributing it to the depletion of smaller spheres between larger spheres, an observation later extended to using polymer-coated spheres or pNIPAM nanogels as soft depletants [26,27]. A more recent theoretical study considering binary mixtures of soft repulsive spheres however predicted stronger depletion, as compared to hard spheres, and also a metastable fluid-fluid phase transition, which is yet to be verified experimentally [28]. Kaplan et al [29] and Dinsmore et al [30] reported that the fluid-solid transition for the larger spheres was promoted at a hard flat wall, due to the enhanced excluded volume effects at the wall, pointing to the importance of geometry consideration.…”
Section: Phase Separations In Binary Collodial Mixtures: Implicationsmentioning
confidence: 92%
“…(4) is the correlation length between nanospheres, taking into consideration the range of interdepletant -soft‖ interactions of range [28]. In the presence of the electric double layer force, Zeng et al proposed that  =  -1 (the Debye length), and we suggest that could be generalised as the range of the soft inter-nanoparticle interaction, e.g.…”
mentioning
confidence: 97%
“…calculations [39][40][41][42][43][44][45]. Recent work has also been devoted to the effects induced by interactions between depletant molecules, such as the investigation of the phase behaviour of non-ideal mixtures of hard spheres with very short-range Yukawa tails [46] and a few studies on the effect of attractive interactions on depletion forces [47][48][49].…”
mentioning
confidence: 99%
“…The first theory for the so-called depletion attraction originates from the work of Asakura and Oosawa in the 1950s [28,29]. For colloidal spheres mixed with non-adsorbing polymer chains, this depletion attraction has been widely studied [30], also for systems with direct colloid-colloid interactions beyond hard-core [31][32][33].…”
Section: Introductionmentioning
confidence: 99%